Моделювання обтікання перешкод методом граткових рівнянь Больцмана при великих числах Рейнольдса - Остапенко, Артем Олексійович; Буланчук, Галина Григорівна (НТУ "ХПІ", 2019)
Розглядається застосування кінетичного підходу до моделювання динаміки в'язкої рідини. Запропоновано метод регуляризації для отримання стійких та фізичних розв'язків при великих числах Рейнольдса до 20000. В основі методу регуляризації закладена медіана фільтрація, що ефективно згладжує аномальні пульсації. Верифікація методу проведена на класичній тестовій задачі про обтікання кругового циліндра. Проведені чисельні експерименти із моделювання течії довкола профілю Nasa 0012 під різними кутами атаки.

The application of the kinetic approach for the viscous fluid flow modeling is considered. A regularization method is proposed for obtaining stable and physical numerical solutions at large Reynolds numbers up to 20,000. The basis of the regularization method is the median filtration that effectively smoothes abnormal ripples and, at the same time, preserves the boundaries of sharp transitions and the structure of the flow. The verification of the method was carried out on the classical test task of the flow around circular cylinder at the Reynolds numbers from 500 to 20000. Numerous experiments were conducted to simulate the flow around the profile of Nasa 0012 at different angles of attack.
Simulation of the flow over obstacles with the lattice Boltzmann method at large Reynolds numbers
Keywords: в'язка рідина; регуляризація; круговий циліндр; профіль; viscous flow; Boltzmann equation; regularization; circular cylinder